THE INFLUENCE OF THE WORK ENVIRONMENT AND DISCIPLINE ON THE WORK PRODUCTIVITY OF REGIONAL HOSPITAL EMPLOYEES KUMPULAN PANE - Rodi Syafrizal (PT. Radja Intercontinental Publishing, 2020)
The aim of this research is to determine the influence of the work environment and discipline on the work productivity of RSUD employees. Pane Group. The population in this study were ASN employees of the Kumpulan Pane Regional Hospital, totaling 35 respondents. The data source in this study came from primary data, namely from the results of collecting questionnaires which were filled in directly by the respondents. Hypothesis testing uses multiple regression analysis on the SPSS version 25 application. The results of this research show that partially the work environment has no effect on work productivity and discipline has a significant effect on employee work productivity. Meanwhile, simultaneously the work environment and discipline influence the work productivity of ASN employees at Kumpulan Pane Hospital.